Polyether-Based Supramolecular Electrolytes With Two-Dimensional Boroxine Skeleton - Yoshizawa-Fujita, Masahiro; Horiuchi, Shunsuke; Uemiya, Tamao; Ishii, Jun; Takeoka, Yuko; Rikukawa, Masahiro (Frontiers in Energy Research, 2021)
Solid polymer electrolytes mainly based on polyethers have been actively investigated over 40 years to develop safe, light, and flexible rechargeable batteries. Here, we report novel supramolecular electrolytes (SMEs) composed of polyether derivatives and two-dimensional boroxine skeleton synthesized by the dehydration condensation of 1,4-benzenediboronic acid in the presence of a polyether with diamines on both chain ends. The formation of SMEs based on polyether derivatives and boroxine skeleton was confirmed by Fourier transform infrared (FT-IR) spectroscopy, X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), and thermogravimetric analysis (TGA). Linear sweep voltammetry (LSV) and cyclic voltammetry (CV) were performed to evaluate the electrochemical properties of SMEs with given amounts of lithium bis(trifluoromethylsulfonyl)amide (LiTFSA). SME/LiTFSA composite electrolytes exhibited a stable lithium plating/striping process even after 100 cycles. The current density increased with an increasing number of cycles.